Análise da viabilidade financeira de implementação de uma empresa de confeitaria no município de Tupanci do Sul – RS - Goubeth, Maikely Marcon (2021)
The financial feasibility study is an essential tool in opening a business, as with the use of this technique it is possible to project the project in front of the market. It is essential to note that the entrepreneur is extremely important to the economy, and that he is the individual who takes the risks to start the venture, that is, the one who must take the initiative and be responsible for their own decisions. In order to have a profitable venture, it is necessary to look for the results and analyze them to conclude if they are really valid and correspond to the objectives. In this context, the present work seeks to project the costs and revenues, cash flow and return on investment, in the assessment of the financial feasibility of installing a confectionery shop, so that it can be concluded whether it will really be profitable. For this, the knowledge acquired during the course will be used. Finally, it is noteworthy that after the case study, the business is financially viable, having great market potential and being able to achieve the objectives proposed by the entrepreneur.